2002
DOI: 10.1590/s0103-50532002000400006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of scavengers on the photocatalytic digestion of organic matter in water samples assisted by TiO2 in suspension for the voltammetric determination of heavy metals

Abstract: A influência de scavengers de elétrons e de lacunas positivas na digestão fotocatalítica de matéria orgânica na presença de partículas de TiO 2 em suspensão, foi investigada. O processo, que visa a determinação eletroquímica de traços de metais pesados em amostras de água, foi acompanhado mediante observação da recuperação da onda voltamétrica de Cd(II) em presença de EDTA, escolhido como ligante-modelo na simulação do efeito complexante da matéria orgânica natural. Confirmouse o poder acelerador de O 2 , que … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
1
10
0
2
Order By: Relevance
“…9). The enhancing effect of dissolved oxygen on the catalysts performance has also been reported by Cavicchioli et al 28 The results obtained in this work were in agreement with those reported by Benacherine et al who studied the photodegradation of amoxicillin by Goethite (a-FeOOH). They reported that dissolved oxygen increased the degradation efficiency.…”
supporting
confidence: 93%
“…9). The enhancing effect of dissolved oxygen on the catalysts performance has also been reported by Cavicchioli et al 28 The results obtained in this work were in agreement with those reported by Benacherine et al who studied the photodegradation of amoxicillin by Goethite (a-FeOOH). They reported that dissolved oxygen increased the degradation efficiency.…”
supporting
confidence: 93%
“…Dissolved oxygen was one of the parameters, which had significant effect on the degradation of naproxen. Produced OH° radicals via dissolved oxygen, which ameliorated the degradation process as the following reactions . normalO 2 + normale normalO 2 normalO 2 + normalh + normalH 2 normalO 2 + normalO 2 normalO 2 + normale normalH 2 normalO 2 + normalH + normalH 2 normalO 2 + normale OH + OH …”
Section: Resultsmentioning
confidence: 99%
“…The proposed kinetic model bear some similarities with the L-H equation. Since, the organic scavengers were used to minimize the electron-hole recombination during photo-excitation process [46,47], therefore the k d % 0 and the above equation can be simplified into Eq. (10):…”
Section: Photo Adsorption Kinetic Studiesmentioning
confidence: 99%